2017
DOI: 10.1007/s40368-016-0266-4
|View full text |Cite
|
Sign up to set email alerts
|

Why do children and adolescents neglect dental flossing?

Abstract: Low compliance and difficulties in flossing among children and adolescents seemed to be more related to lack of motivation, although problems concerning manual skills were also observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…Similar findings have been reported by [18]. Another study, from Brazil [19], reported similar results for interdental cleaning: the adolescents had been instructed in the importance of using dental floss, but compliance was low. This was attributed to poor motivation, although lack of manual dexterity was also noted.…”
Section: Discussionsupporting
confidence: 82%
“…Similar findings have been reported by [18]. Another study, from Brazil [19], reported similar results for interdental cleaning: the adolescents had been instructed in the importance of using dental floss, but compliance was low. This was attributed to poor motivation, although lack of manual dexterity was also noted.…”
Section: Discussionsupporting
confidence: 82%
“…In agreement with this result, a study carried out with Iranian adolescents showed that all the evaluated youngsters had a high index of dental biofilm and 93% of them had gingival bleeding [23]. These results confirm the fact that adolescence is a risk phase for oral diseases [18], reinforcing the need for intervention studies in this age group.…”
Section: Discussionsupporting
confidence: 81%
“…A previous study conducted with young Indians also showed a high knowledge (90.9%) in oral health [17]. This result suggests that, at present, adolescents have easy access to the media where aspects related to oral health can also be transmitted [18]. However, it is necessary that the acquisition of knowledge is transformed into actions so that the habits are incorporated into the daily life of the individual [19].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…According to Mottos-Silveira et al [ 25 ], the main reason why flossing is so rarely performed lies in a lack of cooperation of the individuals, and any manual difficulty encountered with the flossing procedure itself would apparently be a minor issue. It is up to dentists and dental hygienists to educate adolescents and motivate them to make flossing a habit, also reminding the parents of its importance if necessary.…”
Section: Discussionmentioning
confidence: 99%